2015
DOI: 10.3892/mmr.2015.4541
|View full text |Cite
|
Sign up to set email alerts
|

SOX18 knockdown suppresses the proliferation and metastasis, and induces the apoptosis of osteosarcoma cells

Abstract: Sex determining region Y‑box 18 (SOX18) has been found to be overexpressed in several types of tumor. However, the molecular mechanism underlying the biological function of SOX18 in osteosarcoma remains to be elucidated. The present study aimed to elucidate the roles of SOX18 in regulating the biological behavior of osteosarcoma cells. First, SOX18 mRNA expression was analyzed in osteosarcoma tissues using reverse transcription‑quantitative polymerase chain reaction (RT‑qPCR). The results demonstrated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Thus, future screening approaches in search of SOX18/PROX1 inhibitors are required and may reveal compounds with improved specificity. SOX18 overexpression is observed in different cancer types (12)(13)(14)(15)(16)(17)(18) causing enhanced migration, adhesion and invasivity (45). This underscores the importance to determine specific SOX18-targeting strategies (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future screening approaches in search of SOX18/PROX1 inhibitors are required and may reveal compounds with improved specificity. SOX18 overexpression is observed in different cancer types (12)(13)(14)(15)(16)(17)(18) causing enhanced migration, adhesion and invasivity (45). This underscores the importance to determine specific SOX18-targeting strategies (20).…”
Section: Discussionmentioning
confidence: 99%
“…SOX18 directly regulates (among other target genes) the transcription of prospero homeobox protein 1 (PROX1), which itself determines the differentiation from blood vessels to lymphatic vessels during embryonic development (7)(8)(9)(10)(11). Furthermore, as SOX18 is overexpressed in various cancer entities (12)(13)(14)(15)(16)(17)(18), this additionally renders SOX18 a candidate target to block vascularisation and metastasis. Thus, a screening approach was undertaken to identify small molecules that inhibit SOX18.…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression of the SOX18 transcription factor was observed in osteosarcoma cells, a fact that may be of great importance in the future in the diagnosis and therapy of this type of malignant tumor (56). In the in vitro and in vivo tests proposed by Wu et al, the SOX18 expression was effectively silenced in the human osteosarcoma cell lines U2OS and MG63, which resulted in a decrease in the cancer cells' ability to form metastases and inhibited tumor growth, thus confirming the role of SOX18 in tumor cell proliferation.…”
Section: Osteosarcomamentioning
confidence: 98%
“…In the in vitro and in vivo tests proposed by Wu et al, the SOX18 expression was effectively silenced in the human osteosarcoma cell lines U2OS and MG63, which resulted in a decrease in the cancer cells' ability to form metastases and inhibited tumor growth, thus confirming the role of SOX18 in tumor cell proliferation. Moreover, it was noted that the inhibition of the SOX18 expression results in a cell cycle arrest in the S phase, and thus results in tumor cell apoptosis (56). Furthermore, there was a reduction of the osteosarcoma cell adhesion and migration capacity.…”
Section: Osteosarcomamentioning
confidence: 99%
“…Yang et al and Cai et al indicated that SOX3 acted as an oncogene in human epithelial ovarian cancer (9) and esophageal squamous cell carcinoma (ESCC) (10). Although other members of the SOX family, including SOX2 (11,12), SOX9 (13) and SOX18 (14), have been found to be involved in the development of osteosarcoma, the expression and biological function of SOX3 in osteosarcoma remain unclear.…”
Section: Introductionmentioning
confidence: 99%